Mild ultrasound-assisted alkali de-esterification modified pectins: Characterization and structure–activity relationships in immunomodulatory effects - Huan Guo; Dong Li; Baohe Miao; Kanglin Feng; Guijing Chen; Renyou Gan; Zhiliang Kang; Hong Gao (Ultrasonics Sonochemistry)
Apple pectin (AP), a well-established dietary fiber, offers significant health benefits, particularly in immunomodulation. However, the structure–activity relationship (SAR) in this context remains poorly understood. This study aimed to elucidate the impact of varying degrees of esterification (DE) on AP’s SAR in immunomodulatory activity. AP-Es (AP-E1, AP-E2, AP-E3) with different DE were prepared using mild ultrasound-assisted alkali de-esterification, followed by SAR analysis. Results revealed that AP-E3, with the lowest DE (5.08 ± 0.22 %), demonstrated a significant reduction in homogalacturonan (HG) domains and a corresponding increase in rhamnogalacturonan-I (RG-I) domains, which coincided with enhanced immunomodulatory effects. The molecular weights of AP-E1, AP-E2, and AP-E3 were determined to be 30.94 ± 0.83 kDa, 27.61 ± 0.65 kDa, and 22.17 ± 0.57 kDa, respectively. To further explore the underlying mechanism, transgenic zebrafish with fluorescent macrophages were utilized. A positive correlation was observed between AP-E3 concentration and the number of fluorescent microspheres engulfed by macrophages. Additionally, AP-E3 significantly upregulated the expression of key immune response genes (tnf-α, il-1β, il-6, cox-2, inos, and nf-κb) and restored the gut microbiota composition and abundance in chloramphenicol-induced immunocompromised zebrafish. Metabolomics analysis revealed that AP-E3 effectively restored metabolic homeostasis by activating multiple signaling pathways associated with signal transduction, immune regulation, and metabolism. These findings highlight the potential of low-esterified AP enriched with RG-I domains as a promising candidate for applications in immune modulation and gut health management.